Influence of skills' training methodic with the application of interdisciplinary connections on motor fitness of senior pupils in light athletic - Abdel Baset Al-Ravashdeh; Zh.L. Kozina; T.A. Bazilyuk; A.S. Ilnickaya (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: determination of influence of technologies of motor and intellectual aspects' impact on process of basic light athletic movements' development. Material: in the research 2 groups of pupils participated: control (n = 22 -girls, n=34 - boys) and experimental (n = 21 - girls and n=34 - boys). Results: we have shown comparison of basic light athletic movements and movements in wildlife. We compared movements in sports with their physical analogues. Main characteristics of basic movements in light athletic have been defined. Methodic of rising of theoretical knowledge level about light athletic exercises has been presented. Conclusions: it is recommended to apply complex methodic of motor actions' training. The methodic combines practical trainings with theoretical knowledge about main laws of movements in wildlife.